Production of protons and light nuclei in Au + Au collisions at √sNN = 3 GeV with the STAR detector - Abdulhamid, Muhammad Ibrahim; Deppner, Ingo Martin; Herrmann, Norbert; Kisel, Ivan; Leung, Yue; Söhngen, Yannick; Weidenkaff, Philipp (Physical review, 2024)
We report the systematic measurement of protons and light nuclei production in Au +Au collisions at √𝑠𝑁⁢𝑁=3GeV by the STAR experiment at the Relativistic Heavy Ion Collider (RHIC). The transverse momentum (𝑝𝑇) spectra of protons (𝑝), deuterons (𝑑), tritons (𝑡), 3He, and 4He have been measured from midrapidity to target rapidity for different collision centralities. We present the rapidity and centrality dependence of particle yields (𝑑⁢𝑁/𝑑⁢𝑦), average transverse momentum (⟨𝑝𝑇⟩), yield ratios (𝑑/𝑝, 𝑡/𝑝,3He/𝑝, 4He/𝑝), as well as the coalescence parameters (𝐵2, 𝐵3). The 4⁢𝜋 yields for various particles are determined by utilizing the measured rapidity distributions, 𝑑⁢𝑁/𝑑⁢𝑦. Furthermore, we present the energy, centrality, and rapidity dependence of the compound yield ratios (𝑁𝑝×𝑁𝑡/𝑁2𝑑) and compare them with various model calculations. The physics implications of these results on the production mechanism of light nuclei and the QCD phase structure are discussed.
Gesehen am 24.02.2026
Im Titel steht "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt